An Integrated Approach to Managing Spare Parts Inventory: A Case Study - Vázquez Carrillo, Diana (2014)
Spare parts have become crucial for the proper functioning of professional equipment and ensuring their availability in stock implies overcoming the trade-off between high service levels and low inventory costs. Since spare parts are usually highly varied –with different costs and demand patterns–, the proper categorisation of the relevant stock keeping units (SKUs) is essential to align the inventory management system with their distinctive attributes. Moreover, an important issue involved in the management of spare parts is that of coping with the demand intermittency that is characteristic of this industry in order to facilitate decision making with respect to forecasting and stock control. This paper presents a stocking approach integrating the classification, demand forecasting and stock control policies for the improvement of the current spare parts management system at a small reseller company in Mexico. To provide insight into the empirical utilisation of inventory management theory, the proposed categorisation, forecasting and inventory control techniques are evaluated using real data.